2015
DOI: 10.1098/rstb.2014.0231
|View full text |Cite
|
Sign up to set email alerts
|

Comparative oncology: what dogs and other species can teach us about humans with cancer

Abstract: One contribution of 18 to a theme issue 'Cancer across life: Peto's paradox and the promise of comparative oncology'. Over 1.66 million humans (approx. 500/100 000 population rate) and over 4.2 million dogs (approx. 5300/100 000 population rate) are diagnosed with cancer annually in the USA. The interdisciplinary field of comparative oncology offers a unique and strong opportunity to learn more about universal cancer risk and development through epidemiology, genetic and genomic investigations. Working across … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
341
0
17

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 315 publications
(363 citation statements)
references
References 174 publications
5
341
0
17
Order By: Relevance
“…It was shown that besides numerous similarities in tumor biological behavior, parallel genetic features of human and canine osteosarcoma cells also exist (Mueller et al 2007, Rowell et al 2011. So, Rottweilers can be an excellent oncologic animal model for researches on human OSA (Fenger et al 2014, Schiffman andBreen 2015).…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that besides numerous similarities in tumor biological behavior, parallel genetic features of human and canine osteosarcoma cells also exist (Mueller et al 2007, Rowell et al 2011. So, Rottweilers can be an excellent oncologic animal model for researches on human OSA (Fenger et al 2014, Schiffman andBreen 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Strong similarities in cancer biology between dogs and humans include patterns of response or resistance to conventional therapy, as well as metastasis and recurrence (4). At the histological level, numerous specific cancers are functionally identical in dogs 1 and humans (osteosarcoma, mucosal melanoma, non-Hodgkin lymphoma, bladder cancer, and others) (4-7).…”
Section: Workhop Sessions: Gap Analysismentioning
confidence: 99%
“…Canine studies are, however, largely prohibitive in terms of costs and scale, severely limiting their routine application in research studies. Moreover, significant differences remain between canine and human osteosarcomas [120].…”
Section: Primary Bone Malignancymentioning
confidence: 99%